COMPARISON OF THE COMPLETENESS AND TIMELINESS OF FOODBORNE ILLNESS OUTBREAK INVESTIGATION INTERVIEWS CONDUCTED BY STATE VERSUS COUNTY LEVEL AGENCIES - Boline, Sarah (My University, 2017)
This field experience report summarizes my experience as a student intern at the Kansas Department of Health and Environment (KDHE), Topeka, Kansas. This field experience was in partial fulfillment of the requirements of the Master of Public Health Program at Kansas State University. During the Summer of 2016, I shadowed epidemiologists, participated in day-to-day operations, and assisted with various duties. During the internship, I conducted a capstone research project under the direction of Sheri Tubach, Director of Infectious Disease Epidemiology and Response in the Bureau of Epidemiology and Public Health Informatics at the Kansas Department of Health and Environment. The objective of this project was to compare the completeness and timeliness of foodborne illness outbreak investigation interviews conducted at the state versus county level. Completeness refers to the number of questions completed on the outbreak investigation interviews. Timeliness refers to how many days after being lab-confirmed it took to contact the case, start the outbreak investigation interview, and complete the outbreak investigation interview. This project used information from lab-confirmed Salmonella and STEC cases in Kansas that were interviewed between January and June of 2016. The state of Kansas adopted a centralized outbreak investigation interview system in January 2016. Each county in Kansas had the opportunity to pass the responsibility of conducting outbreak investigation interviews to KDHE or continue to perform outbreak investigation interviews at the county level. Four counties opted to continue conducting interviews at the county level. The results of this study show that KDHE and the county jurisdiction had similar completeness of outbreak investigation interview questions. The results also show that KDHE completed interviews in a more timely manner than did the counties. The goal of KDHE is to contact a lab-confirmed case within 24 hours of being lab-confirmed, start the outbreak investigation interview in less than three days of being a lab-confirmed case, and complete the outbreak investigation interview within five days of being a lab-confirmed case. KDHE started outbreak investigation interviews for Salmonella cases an average of 2.6 days after a case was lab-confirmed and the county took an average of 9.2 days after the case was lab-confirmed. KDHE completed the interviews at an average of 2.7 days after being lab-confirmed while it took the county jurisdiction an average of 9.8 days to complete. When comparing STEC cases, it took KDHE an average of 3.0 days to start the interview after the case was lab-confirmed while it took the county jurisdiction an average of 9.3 days to complete the outbreak investigation interview. KDHE completed their outbreak investigation interviews for STEC in an average of 3.8 days after being a lab-confirmed case and it took an average of 9.9 days for the county jurisdiction to complete the outbreak investigation interviews. KDHE performed outbreak investigation interviews in a more timely manner than county jurisdiction. Based on the results of this study, a centralized outbreak investigation interview process conducted centrally by KDHE would be beneficial to meeting the KDHE goal of 100 percent completeness of outbreak investigation interviews as well as meeting the goal of conducting interviews within three days and completing the interview within five days of a lab-confirmed case. With a centralized outbreak investigation interview system in place, the same employees would be responsible for all outbreak investigation interviews and consistency among the interviews would help reach the KDHE goal of 100 percent completeness as well as contact a case within 24 hours of being lab-confirmed, set up an interview within three days of being lab-confirmed, and complete the outbreak investigation interview within five days of being a lab-confirmed case.
Keywords: Salmonella; STEC; KDHE; Interview; Completeness and Timeliness